Pedalling Out of Sociocultural Precariousness: Religious Conversions amongst the Hindu Dalits to Christianity in Nepal - Pariyar, Bishnu (Religions, 2021)
Christian conversion has become a major topic of discussion amongst academics, religious leaders, and policymakers alike in recent decades, especially in developing countries. Nepal has witnessed one of the highest rates of Hinduism to Christianity conversion in South Asia. Whilst there are no legal restrictions for religious conversion in Nepal, the conversion from Hinduism to Christianity appears to be disproportionately higher amongst Dalit communities in Nepal. However, religious conversion amongst Nepalese Dalits is yet to be fully understood. This research uses mixed methodologies of data collection and analysis to explore various issues related to religious conversion amongst Hindu Dalits into Christianity in Nepal. Results indicate whilst elderly and female Dalits tended to convert to Christianity, a range of factors specific to personal and communal biographies including social, cultural, emotional, and spiritual interplay together to shape the process of religious conversion amongst the Dalits. The paper concludes that the study of religious conversion should consider a range of sociocultural factors to fully understand the dynamics of religious conversion amongst Dalits.